THE THERMOELECTRIC SOLAR PANELS - R. Ahiska; L. I. Nykyruy; G. Omer; G. D. Mateik (Vasyl Stefanyk Precarpathian National University, 2016)
In this study, load characteristics of thermoelectric and photovoltaic solar panels are investigated and compared with each other with experiments. Thermoelectric solar panels converts the heat generated by sun directly to electricity; while, photovoltaic solar pales converts photonic energy from sun to electricity. In both types, maximum power can be obtained when the load resistance is equal to internal resistance. According to experimental results, power generated from unit surface with thermoelectric panel is 30 times greater than the power generated by photovoltaic panel. From a panel surface of 1 m2, thermoelectric solar panel has generated 4 kW electric power, while from the same surface, photovoltaic panel has generated 132 W only.